Effect of Sn Doping on Pd Electro-Catalysts for Enhanced Electro-Catalytic Activity towards Methanol and Ethanol Electro-Oxidation in Direct Alcohol Fuel Cells - Cyril Tlou Selepe; Sandile Surprise Gwebu; Thabo Matthews; Tebogo Abigail Mashola; Ludwe Luther Sikeyi; Memory Zikhali; Nobanathi Wendy Maxakato (Nanomaterials, 2021)
Carbon nano-onions (CNOs) were successfully synthesized by employing the flame pyrolysis (FP) method, using flaxseed oil as a carbon source. The alcohol reduction method was used to prepare Pd/CNOs and Pd-Sn/CNOs electro-catalysts, with ethylene glycol as the solvent and reduction agent. The metal-nanoparticles were supported on the CNO surface without adjusting the pH of the solution. High-resolution transmission electron microscopy (HRTEM) images reveal CNOs with concentric graphite ring morphology, and also PdSn nanoparticles supported on the CNOs. X-ray diffractometry (XRD) patterns confirm that CNOs are amorphous and show the characteristic diffraction peaks of Pd. There is a shifting of Pd diffraction peaks to lower angles upon the addition of Sn compared to Pd/CNOs. X-ray photoelectron spectroscopy (XPS) results also confirm the doping of Pd with Sn to form a PdSn alloy. Fourier transform infrared spectroscopy (FTIR) displays oxygen, hydroxyl, carboxyl, and carbonyl, which facilitates the dispersion of Pd and Sn nanoparticles. Raman spectrum displays two prominent peaks of carbonaceous materials which correspond to the D and G bands. The Pd-Sn/CNOs electro-catalyst demonstrates improved electro-oxidation of methanol and ethanol performance compared to Pd/CNOs and commercial Pd/C electro-catalysts under alkaline conditions.